QUESTIONNAIRES DONE WITH SPECIALISTS AND RESIDENTS ON FACTORS THAT MAY AFFECT BONDING STRENGTH DURING BONDING PROCEDURE IN ORTHODONTICS - Mahmoud El Saafin; Marius Hack; Alexandra Haj; Mariana Pacurar (Amaltea Medical Publishing House, 2018)
The aim of this study is to evaluate the most commonly used method and technique in fixed orthodontic treatment by making a comparison between questionnaires applied in our Orthodontic department and those applied to orthodontic specialists. Material and methods: 9 self-reported questions were used as tools for the intended evaluation, which were taken from questionnaires that were already recognized to be adequate and accurate. The conclusion of this study showed that one of the highest percentages (52%) revealed in this study was in pumice prophylaxis. Nevertheless, a smaller number of orthodontists (11%) said that they used Fluoridated prophylaxis paste, which was the lowest percentage of material used in polishing procedure, so the majority of orthodontists (specialists and residents) avoid to use fluoridated prophylaxis paste. 100% of orthodontists in this study used phosphoric acid having a concentration range from 35% to 37% with a demineralization time between 15 and 30 seconds, LED light cure was unanimously used by both orthodontic residents and specialists because it presents more advantages than other light cure units. A high percentage (93%) of orthodontists used a curing time between 10 and 25 seconds for the polymerization of the primer and adhesive material, Curing time has inversely proportional with light intensity. The light intensity and radiation exposure time are directly proportional with the total amount of energy supplied. The vast majority of orthodontists (57%) used the low speed hand piece to remove the remnant adhesive material so as to avoid any damage to that could be caused to the enamel surface.